Media Interaktif Pembelajaran Sejarah Kepahlawanan Petra - Kevin Alfian Santoso; Andreas Handojo; Kristo Radion Purba (Jurnal Infra, 2016)
The process of learning the lessons of history are often regarded as tedious, because the lessons of history study the events that happened in the past. Moreover, history lessons are also taught only by using an image or text. Therefore, in order that history lessons can become more attractive in it’s teaching, multimedia applications were made to teach the history interactively.This application resemble the learning system of Pattimura heroic history more interactive and interesting, because users are actively involved in the learning process. The teaching of the history starts from the birth of Pattimura, until death of Pattimura. In this application, there are also tests made, so the user can remember about the material that has been provided. This application is created using Adobe Flash CS6 and actionscript 3 as a programming language. Based on the results of testing of the applications and questionnaires, applications can be run by fully and strongly supports the process of understanding the historical material. This application adds to the interest in learning from the user, because of the interesting animation, and easy to use application. Users who doesn’t read narrative and do the applications in haste would have some difficulties to obtain a good final score.